Lkjhgf

Disponível somente no TrabalhosFeitos
  • Páginas : 2 (293 palavras )
  • Download(s) : 0
  • Publicado : 15 de outubro de 2011
Ler documento completo
Amostra do texto
σ=
E=

F = S ( e + 1) A

ε = ln

A D L = ln 0 = 2.ln 0 = ln ( e + 1) L0 A D

ε=



dε v = dt L
• m

ν=
G=
1 3

∆S ∆e −εtransversal

ε longitudinal
E 2.(1 + ν )

σ x τ yx τ zx σ ij = τ xy σ y τ zy τ xz τ yz σ z
εX =
1 σ X − ν (σ Y + σ Z ) E

σ = H. ε

()

n

σ LE =C. ε

ε v = ε x + ε y + ε z = (σ x + σ y + σ z ) .
1 3

1 − 2.ν E

2 2 2 τ oct = . (σ x − σ y )2 + (σ y − σ z )2 + (σ z − σ x )2 + 6.(τ xy + τ yz+ τ zx ) = . (σ 1 − σ 2 )2 + (σ 2 − σ 3 )2 + (σ 3 − σ 1 )2

σ oct =
U0 =

σx +σy +σz
3

=

σ1 + σ 2 + σ 3
3

1 ν 1 2 2 2 2 2 2 . σ x + σ y+ σ z − . (σ x σ y + σ y σ z + σ x σ z ) + . τ xy + τ xz + τ yz 2E E 2G

(

)

(

)

U0 =

1 2 2 . σ 12 + σ 2 + σ 3 − 2ν (σ 1σ 2 + σ 2σ 3 +σ 1σ 3 ) 2E

σ VM = σ VM = σ=
1 2

1 2

. (σ 1 − σ 2 ) + (σ 2 − σ 3 ) + (σ 3 − σ 1 )
2 2 2 2 2

2

1 2

2 2 2 . (σ x − σ y ) + (σ y − σ z )+ (σ z − σ x ) + 6 τ xy + τ xz + τ yz

(

)

1 2

2 2 2 2 . (σ 1 − σ 2 ) + ( σ 2 − σ 3 ) + (σ 3 − σ 1 ) 2

1 2

ε=

2 2 2 2 . (ε 1 − ε 2) + (ε 2 − ε 3 ) + (ε 3 − ε1 ) 3

1 2

w .h0 .v 0 = w .h1.v1

L = R.∆h

∆hMAX = µ 2 .R

r =

h0 − h1 h0

s=

v1 − v r vr

α=

∆h Rsenα N =
C.FS w .∆h

µ.senα + cos α − 1 2µ
C= 16 1 − ν 2

h=

h0 + h1 2

λ=

λQUENTE = 0,50 a → L λFRIO = 0,45

R / = R. 1 +

(

π.E
µ .L
h

)

hMIN =

(
− 1 .w .L

7 µR .σ LE E 1−ν 2

)

MT = 2.FS .a
W = 4π .a.FS .n

FS = pR .AC =

2.σ LE 3

h e µ.L

tracking img